Understanding the Etiologies of Pancytopenia in Pediatric Patients: A Cross-Sectional Study - Ullah, Inam; Khan, Muhammad Sohaib; Muhammad Fayaz; Khan, Sher Alam; Khan, Nafees; Tabassum, Rabia (Indus Journal of Bioscience Research, 2025)
Introduction: Pancytopenia is not uncommon in children and is termed as a decrease in the production of hemoglobin, platelets and white blood cells resulting in anemia, thrombocytopenia and leucopenia. Wide variety of conditions leads to pancytopenia ranging from benign conditions to malignant diseases that determine the underlying management. Objective: To determine the etiology of pancytopenia in the pediatric population. Methodology: The current study was conducted at pediatric department of Mardan Medical Complex, Mardan spanning from February 2021 to August 2021. This cross-sectional study includes 131 patients labelled as case of pancytopenia aged 1 to 15 years. Full blood count already done was tracked down and recorded in a pre-designed proforma and a bone marrow examination was done for all patients. Data was analyzed using SPSS 20. Results: The mean age was 6.4 years ± 4.1. males were predominant with frequency of 79(60.3%) and females were. 52(39.7%). The predominant symptom was fever with frequency of 86(65.6%) followed by pallor, petechiae/bruises, epistaxis, generalized weakness and bone pains. Aplastic anemia was the prevalent etiology and were reported in 47(35.9) of cases, 24(18.3%) of patients were diagnosed with megaloblastic anemia. No obvious cause was identified in 6(4.6%) of cases. Conclusion: Pancytopenia is a not an uncommon entity and delineating the etiological spectrum is crucial in the management and prognosis of patient. Aplastic anemia was the most prevalent cause followed by megaloblastic anemia.